Thrombotic Thrombocytopenic Purpura in Oman: Disease Burden and Outcomes - Samata Al Dowaiki; Khalid Al Hashmi; Sulayma Al-Lamki; Muhana Al Muselhi; Murtadha Al-Khabori (Oman Medical Journal)
Objectives: Thrombotic thrombocytopenic purpura (TTP) is a rare, life-threatening autoimmune disorder; limited information about this disease is available from the Middle East. This study aimed to provide a background data on TTP epidemiology in Oman, including its clinical characteristics, disease course, and outcomes. Methods: The study used a longitudinal retrospective observational design, drawing on the electronic patient records of two major hospitals in Muscat from January 2006 to December 2019. Patients who met the diagnostic criteria for TTP were included in the analysis. Results: Over 13 years, 54 patients were diagnosed with TTP, seven (13.0%) of whom experienced a relapse. The incidence of TTP in Oman was 1.8 cases per million population per year, mainly affecting women aged 30–50 years. ADAMTS-13 testing in 23 (42.6%) cases revealed enzyme deficiency in six patients and acquired autoantibodies in 10 patients. Treatments included steroids (94.4%), therapeutic plasma exchange (77.8%), rituximab (42.6%), and cyclosporin (18.5%). Among the TTP-induced morbidities, 46.3% of the participants developed deranged kidney function, 24.0% required hemodialysis. Neurological morbidities included seizures (25.4%), confusion (24.1%), stroke (18.5%), and coma (3.7%). Residual neurological deficits occurred in two (20.0%) of 10 patients with stroke. All patients with seizures recovered. The case fatality rate during the study period was seven (13.0%), with 30-day and 90-day mortality rates of 9.3% and 13.0%, respectively. Conclusions: Though TTP was found to be rare in Oman, the affected patients were at risk of developing serious renal and neurological complications. The unusually low prevalence suggests TTP may be underdiagnosed in Oman.